The role of science and technology in the new international order - Volker Rittberger (Intereconomics, 1978)
The United Nations Conference on Science and Technology for Development (UNCSTD) is to be held in Vienna, 20–31 August 1979. The present article arises from the author's work at the United Nations Institute for Training and Research (UNITAR) on the preparations for this conference.
Keywords: 330; International Order